Editor's Note: Welcoming New Journal Associate Editors - David Cuillier (The Journal of Civic Information, 2024)
The Journal of Civic Information welcomes two new associate editors, Dr. A.Jay Wagner of Marquette University and Dr. Ahmed Alrawi of University of Virginia, who will help the journal increase submissions, quality, and outreach.